Probing Cell Redox State and Glutathione-Modulating Factors Using a Monochlorobimane-Based Microplate Assay - Rezeda A. Ishkaeva; Mohamed Zoughaib; Alexander V. Laikov; Plamena R. Angelova; Timur I. Abdullin (MDPI AG, 2022)
Thiol compounds including predominantly glutathione (GSH) are key components of redox homeostasis, which are involved in the protection and regulation of mammalian cells. The assessment of cell redox status by means of in situ analysis of GSH in living cells is often preferable over established assays in cell lysates due to fluctuations of the GSH pool. For this purpose, we propose a microplate assay with monochlorobimane (MCB) as an available fluorescent probe for GSH, although poorly detected in the microplate format. In addition to the new procedure for improved MCB-assisted GSH detection in plate-grown cells and its verification with GSH modulators, this study provides a useful methodology for the evaluation of cell redox status probed through relative GSH content and responsiveness to both supplemented thiols and variation in oxygen pressure. The roles of extracellular interactions of thiols and natural variability of cellular glutathione on the assay performance were emphasized and discussed. The results are of broad interest in cell biology research and should be particularly useful for the characterization of pathological cells with decreased GSH status and increased oxidative status as well as redox-modulating factors.